Garbage collectors, far from health: A study of dermatitis in Middle Java, Indonesia - Grefima Pramudani; Ipop Sjarifah; Yusuf Ari Mashuri (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Household garbage collectors are one of the groups who are at risk of getting dermatitis due to their work. This study aims to determine the relationship between the length of service and the use of long-sleeved work clothes and gloves with dermatitis on the household garbage collector in Surakarta. This was an observational analytic study using a cross-sectional study. The subjects of the study were household garbage collector in Jebres sub-district, Surakarta. A total of 134 respondents was recruited as samples using simple random sampling. A questionnaire sheet was used to collect individual data and dermatitis status was determined by the doctor’s diagnosis. A Chi-square test was used to investigate the relationship between the length of service and the use of long-sleeved work clothes and gloves with dermatitis. Logistic regression was used to determine factors associated with dermatitis. There was a significant relationship between the length of service with dermatitis p=0.000 (p<0.05). There was also a significant relationship between long-sleeve work clothes and gloves with dermatitis p=0.003 (p<0.05). The multivariable test showed that workers with a long length of service had a higher risk of having dermatitis compared to a short length of service (OR=6,701, p=0.000). It was also showed that more frequent use of long-sleeved work clothes intensity reduces the risk of getting dermatitis compared to sometimes use (OR=0.341, p=0.017). There is a significant association between the length of work and the use of long-sleeved work clothes and gloves with dermatitis on household garbage collectors in Surakarta.